Experimental investigation of multi-band OCT precoding for OFDM-based visible light communications - Hong, Yang; Xu, Jing; Chen, Lian-Kuan (Optics express, 2017)
In this paper, we propose and experimentally demonstrate a channel-independent multi-band orthogonal circulant matrix transform (MB-OCT) precoding, to efficiently combat the severe frequency-selective fading of visible light communications (VLC). The proposed MB-OCT precoding exhibits an attractive ladder-like signal-to-noise-ratio (SNR) profile, thus can significantly reduce system BER by applying different quadrature amplitude modulation (QAM) level to different sub-bands. The impacts of sub-band number, signal bandwidth, and length of cyclic prefix (CP) on bit error rate (BER) of the VLC system are investigated. We experimentally compare BER performance of the proposed MB-OCT precoding with that of the conventional MB discrete Fourier transform (MB-DFT) precoding and the adaptive-loaded discrete multitone (DMT). The results show that the MB-OCT precoding outperforms the MB-DFT precoding and the single-band case for different data rates. Furthermore, it exhibits reduced implementation complexity and comparable BER performance with the adaptive-loaded DMT. For ~700-Mb/s VLC system with 2-m transmission distance, the BER is reduced from 1.53 × 10 to 1.17 × 10 by using the proposed MB-OCT precoding.